Home visit in the context of social vulnerability: people visited perspective - Girlane Mayara Péres; Carmen Leontina Ojeda Ocampo Moré (Revista de Psicología, 2024)
Home visits are an intervention instrument of the Unified Social Assistance System and the main link between teams and families. This qualitative research aimed to understand the experience of home visits, from the perspective of families monitored by the Unified Social Assistance System. So, 12 in-depth interviews were conducted with people from the families visited. The data were organized and analyzed from the perspective of Grounded Theory, with the aid of the software Atlas.Ti 8.4. The results showed families with histories of vulnerabilities and violence, the interviewees were unaware of the reason for the home visit and built ambivalent bonds with the professionals. The need to reflect on the proposal of the community bond and the objectives of home visits, between families and professionals, is highlighted.